Fatores de risco para near miss materno: revisão integrativa [Risk factors for maternal near miss: an integrative review] [Factores de riesgo para near miss materno: revisión integrativa] - Aline Amorim da Silveira; Ana Paula de Assis Sales; Andreia Insabralde de Queiroz Cardoso (Revista Enfermagem UERJ)
Objetivo: sumarizar os principais fatores de risco relacionados ao near miss materno. Método: revisão integrativa da literatura. A busca foi efetuada em 21 de março de 2021, nas bases de dados: NationalLibrary of Medicine - Medline via PubMed; Current Index to Nursing and Allied Health Literature; Science Direct, Elservier’s Scopus, Web of Science e no portal da Biblioteca Virtual de Saúde. Os estudos foram avaliados com a Hierarchy of Evidence for Intervention Studies. Resultados: 12 artigos compuseram a revisão, todos de método quantitativo e idioma inglês. As evidências destacaram como risco para near miss materno: distúrbios hipertensivos, complicações hemorrágicas e a sepse puerperal. Demais achados relacionam-se à distância da moradia e dificuldade de acesso aos serviços de saúde além da baixa escolaridade. Conclusões: os fatores de risco para near miss materno se relacionam com pré-natal inadequado, decorrente de questões geográficas e falta de acesso aos serviços, questões econômicas, educacionais e sociais. Objective: to summarize the main risk factors for maternal near miss. Method: this integrative literature review was performed on March 21, 2021, in the following databases: the National Library of Medicine – Medline via PubMed, the Cumulative Index to Nursing and Allied Health Literature, Science Direct, Elsevier’s Scopus, Web of Science, and the Virtual Health Library portal. Articles were evaluated with the Hierarchy of Evidence for Intervention Studies. Results: the 12 articles reviewed all used quantitative methods and were in English. As risks for maternal near miss, evidence highlighted hypertensive disorders, bleeding complications, and puerperal sepsis. Other findings related to the domicile’s distance from, and difficulty in accessing, health services, as well as low level of education. Conclusions: risk factors for maternal near miss relate to inadequate prenatal care resulting from geographic issues and lack of access to services, plus economic, educational, and social issues. Objetivo: resumir los principales factores de riesgo relacionados con el near miss materno. Método: revisión integrativa de la literatura. La investigación se realizó el 21 de marzo de 2021, en las siguientes bases de datos: NationalLibrary of Medicine - Medline via PubMed; Current Index to Nursing and Allied Health Literature; Science Direct, Elservier’s Scopus, Web of Science y en el portal de la Biblioteca Visrtual de Salud. Los artículos fueron evaluados con la Hierarchy of Evidence for Intervention Studies. Resultados: 12 artículos conformaron la revisión, todos tenían método cuantitativo y estaban en inglés. Se destacaron como riesgos de near miss materno: trastornos hipertensivos, complicaciones hemorrágicas y sepsis puerperal. Otros hallazgos están relacionados con la distancia del hogar y la dificultad para acceder a los servicios de salud, además de la baja escolaridad. Conclusiones: Los factores de riesgo para el near miss materno están relacionados con la atención prenatal inadecuada, como resultado de cuestiones geográficas y la falta de acceso a los servicios, y a cuestiones económicas, educativas y sociales.